Bibliometric analysis of the thermal storage systems research in the last ten years (2018)
In this research we analyze the state of the art of the technological developments that are being presented by the scientific community to mitigate the strong environmental changes with renewable energies. The results obtained by the bibliometric techniques in the period 2007-2018 show that in the 1900 published articles the People's Republic of China presents the highest volume of 32.3% of the total publications, showing a strong influence on the development of energy storage technologies and the availability of materials. The results presented in this article allow us to evaluate the development of researchers in this alternative of energy storage as a replacement to the distribution that is done with traditional methods.